Penggunaan Teknik Pelatihan Dasar di Alam Terbuka untuk Meningkatkan Keterampilan Membaca Puisi Siswa Kelas XII IPS 1 SMA Negeri 16 Pekanbaru - Riora, Haswinta (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2020)
Reading poetry is one of the skills in the field of literature included in the learning of Indonesian language and literature in high school. Reading poetry is not the same as reading in general. Reading poetry requires a special skill, namely a reading expression skill. Reading expression trains students to be creative in expressing a poetic text and creating appreciation, vocal techniques, and appearance that are following the contents of the poetry. Unfortunately, based on the field observation, it found that the poetry reading skills of students in class XII Social Science 1 at SMAN 16 Pekanbaru were still low, as seen from the lack of students’ ability in ensouling, vocal techniques, and performances that did not match the contents of the poetry they read. The problem formulation of this study was whether the use of basic outdoor training techniques can improve students' poetry reading skills and how the changes of students’ behaviors in reading poetry learning after applying basic outdoor training techniques in class XII Social Science 1 at SMAN 16 Pekanbaru? This study aimed to describe the improvement of students' ability in reading poetry and to investigate the changes of students’ behaviors in reading poetry learning after applying basic outdoor training techniques in class XII Social Science 1 at SMAN 16 Pekanbaru. The type of this research was classroom action research. The results of this study show that there was an improvement of students' poetry reading skills with an average score of the cycle I was 69.32 and an average score of the cycle II was 82.97. In other words, there is an increase from cycle I to cycle II of 13.65 points or 19.69%. While the changes in students’ behavior in reading poetry learning experience the addition of positive behavior.